Circadian time‐ and sleep‐dependent modulation of cortical parvalbumin‐positive inhibitory neurons. (7th December 2022) - Zong, Fang‐Jiao; Min, Xia; Zhang, Yan; Li, Yu‐Ke; Zhang, Xue‐Ting; Liu, Yang; He, Kai‐Wen
Abstract: Parvalbumin‐positive neurons (PVs) are the main class of inhibitory neurons in the mammalian central nervous system. By examining diurnal changes in synaptic and neuronal activity of PVs in the supragranular layer of the mouse primary visual cortex (V1), we found that both PV input and output are modulated in a time‐ and sleep‐dependent manner throughout the 24‐h day. We first show that PV‐evoked inhibition is stronger by the end of the light cycle (ZT12) relative to the end of the dark cycle (ZT0), which is in line with the lower inhibitory input of PV neurons at ZT12 than at ZT0. Interestingly, PV inhibitory and excitatory synaptic transmission slowly oscillate in opposite directions during the light/dark cycle. Although excitatory synapses are predominantly regulated by experience, inhibitory synapses are regulated by sleep, via acetylcholine activating M1 receptors. Consistent with synaptic regulation of PVs, we further show in vivo that spontaneous PV activity displays daily rhythm mainly determined by visual experience, which negatively correlates with the activity cycle of surrounding pyramidal neurons and the dorsal lateral geniculate nucleus‐evoked responses in V1. These findings underscore the physiological significance of PV's daily modulation. Synopsis: Unveiling the modulatory mechanism of cortical parvalbumin‐positive neurons (PVs) in the mature mammalian brain is critical for understanding how cognitive function is regulated in normal and diseased brains. Here the behavior of PVs in area V1 of the mouse visual cortex is investigated ex vivo and in vivo and a circadian output is identified. The excitatory and inhibitory synaptic transmissions of PV neurons bidirectionally oscillate in opposite directions during the 24‐h day. Experience and sleep dominate the daily regulation of the excitatory and inhibitory synapses onto PV neurons, respectively. ACh mediates the daily regulation of PV inhibitory synaptic transmission via targeting the presynaptic M1Rs. In line with synaptic modulation of PVs, evoked PV output ex vivo and spontaneous PV activity in vivo are both altered at different times of the day. Functional oscillation of PVs negatively correlates with the spontaneous activity of surrounding pyramidal neurons and dorsal lateral geniculate nucleus‐evoked responses in area V1 of the mouse visual cortex. Abstract : Parvalbumin‐positive neurons of the mouse primary visual cortex are found to be rhythmically regulated in a time‐ and sleep‐dependent manner during the circadian light/dark cycle, mediated by acetylcholine activation of M1 receptors.